The family visits as a proximal process in the development of children in institutional care (Research, Society and Development, 2020)
Aspects of the social interactions observed during the family visit were described, analyzing them from the concept of proximal process of the Bioecological Model of Human Development. Five children from foster care institutions and their families participated. Interviews and observation of interactions were carried out. It was found that the proximal competence processes seem to be related to the way the children remained engaged in building and maintaining the bond with their family members during the visit, translated by the intention to remain together, carrying out activities and establishing affectionate contact. The dysfunctional proximal processes were identified from behaviors such as crying, intense manifestations of the child's suffering at the end of the visit, difficulties in the relationship with their families and in their adaptation to the institution. It is concluded that the interactions that take place over time in the context of the family visit, when they favor the strengthening of affective bonds and promote the well-being of the child, can constitute a proximal process.